2000
DOI: 10.1074/jbc.m007864200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Nuclear Receptor Corepressor Complex, N-CoR, Contains Components of the Mammalian SWI/SNF Complex and the Corepressor KAP-1

Abstract: Transcriptional silencing by many transcription factors is mediated by the nuclear receptor corepressor (N-CoR). The mechanism by which N-CoR represses basal transcription involves the direct or indirect recruitment of histone deacetylases (HDACs). We have isolated two multiprotein N-CoR complexes, designated N-CoR-1 and N-CoR-2, which possess histone deacetylase activity that is mediated by distinct HDACs. Based on Western blotting using antibodies against known subunits, the only HDAC found in the N-CoR-1 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
220
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(235 citation statements)
references
References 59 publications
11
220
3
Order By: Relevance
“…KAP1 can recruit and coordinate many components involved in gene silencing. KAP1-mediated gene silencing involves the recruitment of the histone deacetylase (HDAC) complex [16][17][18], and binding to a histone methyltransferase [19]. Therefore, KAP1 orchestrates the function of these co-repressor complexes to inhibit the transcription of its target genes.…”
Section: Treatment Of Cells With Ifn Induces the Activation Of Jak-stmentioning
confidence: 99%
“…KAP1 can recruit and coordinate many components involved in gene silencing. KAP1-mediated gene silencing involves the recruitment of the histone deacetylase (HDAC) complex [16][17][18], and binding to a histone methyltransferase [19]. Therefore, KAP1 orchestrates the function of these co-repressor complexes to inhibit the transcription of its target genes.…”
Section: Treatment Of Cells With Ifn Induces the Activation Of Jak-stmentioning
confidence: 99%
“…These results suggest that KAP1 may trap STAT3 through STAT3 Ser727 to repress STAT3 transcriptional activation, because STAT3 SA mutant fails to interact with KAP1 as shown in Figure 1d. A direct interaction of KAP1 with HDACs is also proposed to be a mechanism for transcriptional repression by KAP1 (Underhill et al, 2000;Satou et al, 2001;Schultz et al, 2001). It has also been demonstrated that STAT3 associates with HDAC3 and that trichostatin A, an HDAC inhibitor, restores its transcriptional activity (Yuan et al, 2005).…”
Section: Interactions Between Stat3 and Kap1mentioning
confidence: 99%
“…Sequence analysis revealed that one of them encoded the C-terminal region of KAP1 (amino acids 394-835). We examined the distribution of KAP1 in a variety of human cancer cell lines by western blot analysis and found that it was ubiquitously expressed as described previously (data not shown; Underhill et al, 2000). We first examined whether KAP1 binds STAT4 and/or other STATs in mammalian cells.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…TIF1b, also named KAP-1 or KRIP-1, can interact with numerous KRAB domains to enhance KRAB-mediated repression and to silence transcription when it is directly bound to DNA (Collins et al, 2001). Experimental evidence suggests that this silencing activity results from recruitment of a histone deacetylase complex (Underhill et al, 2000) and/or HP-1 proteins that represent chromatin constituents associated with silencing of euchromatic genes (Nielsen et al, 1999;Collins et al, 2001). TIF1b can use its plant homeodomain and bromo-domains to link KZFPs to Mi-2a Involvement of TIPUH1 in HCC FP Silva et al and other components of the nucleosome-remodeling and deacetylase complex (Schultz et al, 2001).…”
Section: Discussionmentioning
confidence: 99%